2021
DOI: 10.1016/j.ebiom.2021.103389
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram to predict evident histological liver injury in patients with HBeAg-positive chronic hepatitis B virus infection

Abstract: Background: HBeAg-positive chronic infection is a unique phase of chronic hepatitis B virus (HBV) infection. Current guidelines advise against starting antiviral treatment for HBeAg-positive chronic hepatitis B virus (HBV) infection patients, some data suggest treating such patients may reduce the risk of hepatocellular carcinoma. We aimed to explore whether these patients can have evident histological liver injury (EHLI), and develop a non-invasive model for identifying EHLI in such patients. Method: We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
(68 reference statements)
3
19
0
Order By: Relevance
“…Similarly, Ishak score was greater in CP1_LI09 and CP1_LI10 cohorts than the corresponding cohorts with CP2. As lower Ishak score represented lower liver injury severity ( 34 , 35 ), it indicated that the cohorts with CP2 profile were with lower liver injury severity.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Ishak score was greater in CP1_LI09 and CP1_LI10 cohorts than the corresponding cohorts with CP2. As lower Ishak score represented lower liver injury severity ( 34 , 35 ), it indicated that the cohorts with CP2 profile were with lower liver injury severity.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, among the 181 patients with HBeAg-positive chronic infection, 60 patients had EHLI; and the proportion of significant fibrosis was higher than that of significant inflammation (33% vs. 8%, p < 0.001). In fact, the authors developed a nomogram to attempt to accurately identify HBeAg-positive chronic HBV infection patients with EHLI, which may respond well to antiviral therapy [ 31 ].…”
Section: Is Hbeag-positive Chronic Infection a Truly Benign Disease P...mentioning
confidence: 99%
“…Patients infected with HBV but have normal ALT levels may exhibit manifestations of liver fibrosis and inflammation upon histological examination ( Chang et al, 2021 ; Liu et al, 2022 ). Previous studies have shown that people with normal ALT levels develop moderate liver tissue inflammation (16.8–40%) and moderate liver fibrosis (24.2–35.9%) ( Ormeci et al, 2016 ; Tan et al, 2017 ; Choi et al, 2019 ; Liu et al, 2022 ), which are associated with a high risk of progression to liver cirrhosis and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018 AASLD guidelines, IT-CHB is defined by HBV DNA > 10 6 IU/mL and normal ALT, while in 2017 and 2019 China guidelines, IT-CHB is defined by HBV DNA > 10 7 IU/mL and normal ALT. However, the ULN of ALT remains controversial with limited value in distinguishing patients experiencing immune tolerance, as the patients are still at risk of liver inflammation or fibrosis when their ALT levels are defined as normal under the lowest ULN standard ( Ormeci et al, 2016 ; Tan et al, 2017 ; Choi et al, 2019 ; Chang et al, 2021 ; Duan et al, 2021 ; Liu et al, 2022 ). Hong et al (2015) speculated that innate immune cell maturation and helper T lymphocyte development existed before intrauterine exposure to HBV during infancy, while another study discovered HBV-specific T lymphocytes in that period ( Bertoletti and Ferrari, 2016 ).…”
Section: Introductionmentioning
confidence: 99%